THE ROLE OF RELIGIOSITY IN THE CONTEXT OF THE ANXIETY TOWARD PANIC BUYING AND COMPULSIVE BUYING IN THE COVID-19 PANDEMIC - Istiasih, Hermin; Faisol, Faisol (Universitas Brawijaya, Indonesia, 2022)
This study explores consumer Panic Buying (PB) and Compulsive Buying (CB) due to consumer anxiety during the COVID-19 pandemic. The role of the religious moderator was also tested to influence consumer attitudes and behavior towards PB and CB to carry out responsible consumption. To empirically test consumer shopping behavior to- wards groceries during the COVID-19 pandemic in East Java, Indonesia. Using the conve- nience sampling approach, data were gathered from young and adult customers in East Java, Indonesia. Through an online survey, 334 customer answers were obtained. The hypotheses were tested using SEM-PLS, which could analyze variables' effect and role in the complex model. The results indicate that anxiety significantly affects panic buying and compulsive buying. Then panic buying has a significant effect on compulsive buying. Further, the results show that anxiety indirectly influences panic buying and compulsive buying. Likewise, religiosity can suppress consumer anxiety when they want to make panic buying and also compulsive buying. This study further contributes as a pilot study on the role of religion in consumer behavior research in a pandemic context, where consumer religiosity can significantly suppress their anxiety in terms of their panic buying and compulsive buying. This study has special implications for retail stores and government agencies for planning retail and social policies that are positive for consumer behavior during a pandemic.